Association between sleep quality and quality of life in nursing professionals working rotating shifts - Palhares, Valéria de Castilho (Faculdade de Saúde Pública da Universidade de São Paulo, 2014)
OBJECTIVE: To analyze the association between sleep quality and quality of life of nursing professionals according to their work schedules. METHODS: A prospective, cross-sectional, observational study was conducted between January and December 2010, with 264 nursing professionals, drawn from 989 subjects at Botucatu General Hospital and stratified by professional category. The Pittsburg Sleep Quality Index and the WHOQOL-bref were administered to evaluate sleep quality and quality of life, respectively. Self-reported demographic data were collected with a standard form. Continuous variables were reported as means and standard deviations, and categorical variables were expressed as proportions. Associations were evaluated using Spearman’s correlation coefficient. The association of night-shift work and gender with sleep disturbance was evaluated by logistic regression analysis using a model adjusted for age and considering sleep disturbance the dependent variable. The level of significance was p < 0.05. RESULTS: Night-shift work was associated with severe worsening of at least one component of sleep quality in the model adjusted for age (OR = 1.91; 95%CI 1.04;3.50; p = 0.036). Female gender was associated with sleep disturbance (OR = 3.40; 95%CI 1.37;8.40; p = 0.008). Quality of life and quality of sleep were closely correlated (R = -0.56; p < 0.001). CONCLUSIONS: Characteristics of the nursing profession affect sleep quality and quality of life, and these two variables are associated.